An exploratory study of the impact of income, health expenditure and pollution on happiness: a global perspective - V. Rasiah, R. Ratneswary; Habibullah, Muzafar Shah; Abdul Hamid, Baharom (Faculty of Economics and Management, Universiti Putra Malaysia, 2012)
There has been a tremendous growth in the number of empirical research on happiness by economists in the past decade. The present study is in the right direction as it explores a relatively intriguing area of research on the “economics of happiness”. The purpose of this study is to find the existence of linkages between happiness and several economic variables. A cross-sectional econometric analysis is employed to examine the impact of the economic variables of income (Gross Domestic Product per capita), health care expenditure and pollution (proxies by CO2 emissions) on happiness across 42 countries in 2006. The findings indicate that a significantly positive relationship exists between happiness and income while pollution has a negative impact on a nation’s wellbeing. The level of health care expenditure however, does not have a significant impact on happiness. The study concludes with an examination of policy implications of the findings.